The Effect of a CD-ROM Interface on Children's Retrieval Performance - Beheshti, Jamshid; Large, Andrew; Breuleux, Alain; Renaud, Andre (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
No abstract available